Epidemiological profile of imported malaria cases in the prevention of reestablishment phase in Sri Lanka. (2nd January 2022) - Dharmawardena, Priyani; Premaratne, Risintha; Wickremasinghe, Rajitha; Mendis, Kamini; Fernando, Deepika
ABSTRACT: Sri Lanka reported the last case of indigenous malaria in October 2012, and received malaria-free certification from WHO in September 2016. Malaria cases have since, shifted from indigenous to imported, and the country remains receptive and vulnerable to malaria. A case-based epidemiological study was conducted on all imported malaria cases reported in the country in 2015 and 2016 with the aim of profiling imported malaria to improve the effectiveness of the surveillance and case management system for malaria. Data were obtained from case reports of the Anti Malaria Campaign, hospital records and laboratory registers. Over the 2 years, 77 imported malaria infections were diagnosed in 54 Sri Lankans and 23 foreign nationals. A majority of the infections were reported among males (93%) in the age group of 21–50 years (85.8%), and all were recent travelers overseas. Most patients were detected by passive case detection, but 10% of cases were detected by Active Case Detection. Only 25% of patients were diagnosed within 3 days of the onset of symptoms. In 32% of patients, the diagnosis was delayed by more than 10 days after the onset of symptoms. Plasmodium falciparum infections manifested significantly earlier after arrival in Sri Lanka than did P.vivax infections. The majority of patients (74%) were diagnosed in the Western Province, which was not endemic for malaria. A third of patients were diagnosed in the private sector. The shift in the epidemiology of malaria infection from before to after elimination has implications for preventing the reestablishment of malaria.